اہل سنت کے غیرمتداول فقہی مکاتب فکر کا تعارف، اصول استنباط اورمعدوم ہونے کےاسباب (ایک مطالعہ) - Khan, Khalid Hameed; Imam-un-Din,; Khan, Dr. Fazal Ilahi (Al-Irfan, 2022)
The chain of prophethood ended with Prophet Muhammad ﷺ. That is, Muhammadiyah Shariat is the last Shariat, no Shariat will come after it. Wherever Allah announced the completion of the religion, He also established the authority of the Prophet's Sunnah. Divine revelation was present in the time of the Prophetﷺ . But the Prophet ﷺopened the door of ijtihad forever for the Muslim Ummah to solve the problems that arose after his death with the idea of ​​the discontinuance of revelation. As a result of which, several jurisprudential religions came into existence. Some of these religions have survived, while others have died out. In the present era, the jurists of the four imams of Ahl al-Sunnah are popular among the people, While most people are unaware of extinct religions. While it is important for the scholars to have knowledge of these uncommon jurisprudential religions, it is also important to realize that the knowledge and jurisprudential stock that was lost with the disappearance of these jurisprudential religions can be understood and searched for again. Earning rights can be used from it. Lack of students, inattention, various political, social, administrative, ideological and regional motivations led to their demise. In this research paper, a brief history of unconventional jurisprudential schools of thought and the reasons for their extinction will be presented.